A quantitative study of the allophanate formation reaction in PIR foams by FT-IR spectroscopy. (November 2022) - Zharkov, Vadim V; Vlasov, Ruslan R
The method for determining the concentrations of the main functional groups in rigid polyisocyanurate (PIR) foams was developed using ATR-FTIR spectroscopy. On the example of a series of rigid PIR foams of isocyanate indexes (II) from 150 to 400, the contents of isocyanate, allophanate and isocyanurate groups was determined. It has been shown that a significant amount of isocyanate groups is accumulated in PIR foams in the form of allophanate, without passing into the target product – isocyanurate; the bulk of the urethane groups is converted to allophanate at high isocyanate indexes. With an increase in the isocyanate index, the conversion degree of isocyanate to isocyanurate decreases and when a certain isocyanate index is attained, reaches the limiting value.